2014
DOI: 10.1016/j.jad.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality in never-depressed patients and the development of major and minor depression after acute coronary syndrome

Abstract: Our data suggests that TDP does not predict the development of depressive disorders in never-depressed patients at their first ACS, when the baseline depression severity was controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…One study, however, found no relation between type D personality and the development of major depression or minor depression in 250 patients who had an acute coronary syndrome [26]. Major or minor depression in this study was measured by the DSM-IV.…”
Section: Discussionmentioning
confidence: 61%
“…One study, however, found no relation between type D personality and the development of major depression or minor depression in 250 patients who had an acute coronary syndrome [26]. Major or minor depression in this study was measured by the DSM-IV.…”
Section: Discussionmentioning
confidence: 61%
“…Risk factors for the development of depression after ACS have been also identified: younger age (Lespérance et al, 1996;Dickens et al, 2004;van Melle et al, 2006); female gender (Doyle et al, 2015); low level of education (Frasure-Smith et al, 2007;Carney et al, 2009); low socio-economic status (Steptoe et al, 2011); having no close friend (Frasure-Smith et al, 2000); being unemployed and living alone (Larsen et al, 2013;Spijkerman et al, 2005a); Type D personality (Martens et al, 2008); psychological vulnerabilities (i.e. exhaustion, fatigue, interpersonal difficulties, cognitive distortions) (Ladwig et al, 1992;Ketterer et al, 1998;Strik et al, 2001;Rieckmann et al, 2006;Stafford et al, 2009;Doyle et al, 2011;Denton et al, 2012) and the presence of depressive symptoms in the few days after an ACS (Di Benedetto et al, 2007;Celano et al, 2012;Marchesi et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…It could be hypothesized that type-D personality participants resort to negative affectivity as an emotional coping strategy, which becomes less responsive once a life-threatening event occurs. In fact, other studies have also found that negative affectivity was unrelated to depressive symptoms following an AMI, 41 and that depression was unrelated to CVD severity in type-D patients. 42 In other words, our data overall suggest that type-D works as a risk factor for cardiac events by amplifying the expression of negative affect, and that this influence becomes diminished once the disease is established.…”
mentioning
confidence: 93%